Demographic Characteristics of Cases with IOFB Presented to a Tertiary Care Centre - Mir Ali Shah, Mohammad Idris, Sadia Ayaz, Hassan Yaqoob, Zubairullah (Pakistan Journal of Ophthalmology, 2015)
Purpose: To determine the demographic characteristics of IOFB presenting to a tertiary care centre of Khyber Pakhtunkhwa for management. Material and Methods: The study was carried out at Department of Ophthalmology, Govt. Lady Reading Hospital, Peshawar from July 2011 to Jan 2013. We received 37 cases from outdoor department for management and were admitted for management. Patients were examined after detailed history and important findings noted. Data was collected on special proforma and was analyzed with the help of SPSS Version16. Results: The study population comprised of 37 cases. Male were 26 (70.2%). . Mean age was 33 ± 12 years. Hammering a chisel was the main cause and it was seen in 15 (40.5%) cases. Labor was the commonest occupation which was seen in 18 (48.6%) cases. No perception of light vision was noted in 11 (29.7%) cases and 09 (24.32 %) cases presented with Perception of light vision. Counting finger or better vision was noted in 17 (46%) cases. Left eye was affected in 25 (67.6%) cases. Conclusion: Duration of trauma was linearly proportion with prognosis for vision. Visual progression was poor in majority of the eyes; delayed presentation and BBI were the top reasons. Key words: IOFB, ocular trauma, visual outcome.